Evaluation of hospitalizations for conditions sensitive to primary care in a university hospital in the Northeast (Research, Society and Development, 2023)
Objective: To outline the epidemiological profile of Hospitalizations for Primary Care Sensitive Conditions (ICSAP) in adults and elderly people, at the Hospital Universitário Alcides Carneiro (HUAC) in Campina Grande, Paraíba, Brazil. Method: This is a cross-sectional study carried out with a sample of adults and elderly people corresponding to the total number of hospitalizations that occurred during the data collection period. The outcome of the study was “Admission for Primary Care Sensitive Conditions – ICSAP”, obtained from the clinical diagnoses present in the Hospital Admission Authorization (AIHs) and/or Medical Records. The independent variables were: sociodemographic conditions; the attributes of Primary Health Care (PHC); the trajectory of care. Data collection was done through interviews and a standardized questionnaire. Descriptive and inferential statistical analyzes were used. Results: Among 196 hospitalizations evaluated, 47 (24.0%) were classified as ACSC. Among the demographic variables, only employment status was associated with ACSC (p